Getting skills right: future-ready adult learning systems (Paris, 2019)
"With digitalisation, deepening globalisation and population ageing, the world of work is changing. The extent to which individuals, firms and economies can harness the benefits of these changes critically depends on the readiness of adult learning systems to help people develop relevant skills for this changing world of work. This report presents the key results from the Priorities for Adult Learning (PAL) Dashboard which facilitates comparisons between countries along seven dimensions of the readiness of adult learning systems to address future skill challenges. Based on the dashboard, the report highlights in which areas action is needed, and policy examples from OECD and emerging countries throughout the report illustrate how these actions could be implemented."